2013
DOI: 10.1186/1471-2164-14-434
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome sequencing of axolotl blastema for identification of differentially expressed genes during limb regeneration

Abstract: BackgroundSalamanders are unique among vertebrates in their ability to completely regenerate amputated limbs through the mediation of blastema cells located at the stump ends. This regeneration is nerve-dependent because blastema formation and regeneration does not occur after limb denervation. To obtain the genomic information of blastema tissues, de novo transcriptomes from both blastema tissues and denervated stump ends of Ambystoma mexicanum (axolotls) 14 days post-amputation were sequenced and compared us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 50 publications
4
62
0
Order By: Relevance
“…2A). These two pathways have previously been implicated in the regulation of programmed cell death and proliferation during regeneration (Gilbert et al, 2013;Godwin et al, 2013;Ho and Whitman, 2008;Lévesque et al, 2007;Rao et al, 2009;Stoick-Cooper et al, 2007;Wu et al, 2013). The miRDeep2 program (Friedländer et al, 2012) was used to align and quantify miRNA reads.…”
Section: Differential Expression During Os Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). These two pathways have previously been implicated in the regulation of programmed cell death and proliferation during regeneration (Gilbert et al, 2013;Godwin et al, 2013;Ho and Whitman, 2008;Lévesque et al, 2007;Rao et al, 2009;Stoick-Cooper et al, 2007;Wu et al, 2013). The miRDeep2 program (Friedländer et al, 2012) was used to align and quantify miRNA reads.…”
Section: Differential Expression During Os Regenerationmentioning
confidence: 99%
“…The ability to detect transcript level changes in a comprehensive and unbiased manner can identify previously unknown coordination between signaling pathways, transcription factors and effector genes required for regeneration. There have been several transcriptome-wide studies of gene expression of both mRNA (Campbell et al, 2011;Hamada et al, 2015;Knapp et al, 2013;Love et al, 2011;Monaghan et al, 2009;Schebesta et al, 2006;Stewart et al, 2013;Wu et al, 2013) and microRNA (miRNA) (Gearhart et al, 2015;Holman et al, 2012;Hutchins et al, 2016;Thatcher et al, 2008) during appendage regeneration. However, none of these studies connected the expression profiles of miRNA to those of mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…It is previously known that regeneration involves controlled expression of peptides and transcripts of signalling molecules at each stage of epimorphosis [18,19,31]. Therefore, to identify the stage-specific expression of peptides, we performed two dimensional gel electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on proteomic profile in regeneration models to unravel the conserved and diverse mechanisms amongst them [16][17][18][19]. It includes the regeneration in axololtl [20,21], Xenopus laevis froglet limb-bud [22,23] and zebrafish caudal fin regeneration [24].…”
Section: Introductionmentioning
confidence: 99%
“…The "general function" category (3,166; 24.37%) represented the largest group, 454 followed by "defense mechanisms" (1,421; 10.94%). Our results showed that genes related to defense 455 functions may be relatively abundant in the transcriptome of O. cruralis, particularly compared to the 456 seven anurans studied by Huang et al (2016) and also to A. mexicanum (Wu et al 2013 Although large genome size renders complete genome sequencing practically unfeasible in many 515 species, such as most amphibians, transcriptome sequencing represents a cost-effective alternative to 516 obtain a large amount of genome-wide data. This can allow advances in the study of ecological and 517 evolutionary processes beyond the limits imposed by the use of small panels of markers.…”
mentioning
confidence: 99%